Pengaruh Akuntabilitas, Transparansi Dan Pastisipasi Masyarakat Terhadap Pengelolaan Dana Desa Di Kecamatan Sukomoro, Kabupaten Nganjuk - Rendi Ardiansyah; Muhammad Taufik Hidayat (P3M Politeknik Negeri Bengkalis, 2024)
The aim of this research is to examine the influence of accountability, transparency and community involvement in village budget administration, particularly in Nganjuk Regency's Sukomoro District villages. With a sample of five villages in Sukomoro District and a population of twelve villages, this study used a quantitative methodology. The Statistical Product and Service Solution (SPSS 22) is used in the test software includes tests for determination tests (R), t tests, F tests, and multivariate linear regression analysis. According to the study's findings, accountability greatly enhances transparency and local finance management, transparency and community involvement significantly improve accountability in village fund management as well.